Clovis keeps his cool - Aronson, Katelyn (Page Street Kids, 2021)
"Clovis used to struggle with his temper, but ever since he took over his late grandmother's china shop, he's been learning how to manage it. He pours tea, listens to soothing music, and always keeps Granny's words in mind: 'Grace, grace, nothing broken to replace.' But when rivals from his football days come to heckle him at the shop, Clovis faces a big challenge that even Granny's words and deep breaths might not be enough for"--